Aspects of a poplar-pasture system related to pasture production in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science at Massey University, New Zealand - Guevara-Escobar, Aurelio (Massey University, 1999)
Widely spaced poplars (Populus deltoides, <100 stems/ha) are the best technology to control soil erosion over 3.7 x 10 6 ha in New Zealand on sedimentary hill soils. To date, the effects of poplars on water, soil and pasture relations are poorly studied. This thesis compared traditional stable open pasture (OP) and widely spaced poplars (5-40 years old) and its grass/legume un-derstorey (PP) based on rainfall partitioning, soil and pasture characteristics. It was concluded that mature PP (>29 years old and 37-40 stems/ha) used more water during November (18 days) as evapotranspiration (ET, 2.7-3.0 mm d-1) than the OP (2.2 mm d-1). Canopy rainfall interception (1.37 mm d-1) was more important than tree transpiration (0.92 mm d-1) or understorey ET (0.4-0.6 mm d-1). Despite the differences in water partitioning, soil water (θ) in the PP was similar or higher than in the OP. The mature PP had lower topsoil θ (0-150 mm) than the OP during 1996 (37 and 43 %v/v, respectively). PP topsoil was drier in January, May and June, but θ was similar to the OP in other months of 1996. During dry weather (1997), θ in the topsoil was higher in the PP than in the OP. Variation in θ around the trees was significant but small in magnitude. PP soil temperature was lower than in OP particularly during summer. Soil pH was higher (0.5-1.2 units) in the PP as were exchangeable cations. Poplar leaf litter decomposition along with poplar N nutrition, reduced soil water leaching and legume N-fixation, all contributed to higher soil pH. Using the legume dry matter (DM) as a proxy of N-fixation, the PP fixed 54% of that in the OP. With the exception of lower total N in the PP, little differences were found in organic C, total N, P or S, or soil P or S fertility, hydraulic conductivity, porosity and water aggregate stability between the OP and PP. Earthworm populations were similar or lower in the PP. Pasture DM accumulation in the mature PP was 60% (6.2 t ha-1 yr-1) of that in OP as the poplar canopy (70% canopy closure ratio) allowed only 20% of the photosynthetically active radiation in the OP to reach the understorey. The legume proportion was similar between the OP and PP, although actual yield was lower in the PP. The PP area had slightly lower grass percentage at the expense of higher comminuted tree debris material. OP forage generally had higher feed value in terms of crude protein, metabolisable energy and in vitro DM digestibility. With the exception of higher soil pH, no difference in other soil or understorey characteristics was found between the OP and PP planted with young poplars. The understorey could take advantage of improved soil water and pH conditions if silvicultural management reduced the shading effect from poplars without impairing soil conservation. Canopy and understorey management options to increase/better utilise pasture DM are discussed.
Keywords: Agroforestry; Poplar; New Zealand